KITENIN recruits Dishevelled/PKCδ to form a functional complex and controls the migration and invasiveness of colorectal cancer cells. Issue 4 (24th July 2008) - Kho, D H; Bae, J A; Lee, J H; Cho, H J; Cho, S H; Lee, J H; Seo, Y-W; Ahn, K Y; Chung, I J; Kim, K K
Abstract : Background and aims: KITENIN was previously reported to promote metastasis in mouse colon tumour models; however, the signalling mechanism of KITENIN at the cellular level was unknown. Here the functional role of KITENIN with respect to colorectal cancer (CRC) cell invasion and its expression in CRC tissues were investigated. Methods: The effect of KITENIN on cell motility was analysed in a migration and invasion assay upon its overexpression and knockdown. Immunoprecipitation was used to elucidate binding partners, and immunohistochemistry was used to study expression levels. Results: KITENIN overexpression enhanced the migration of rat intestinal epithelial cells, whereas a loss of invasiveness was observed in CRC cells after KITENIN knockdown. Mechanically, KITENIN served as a scaffolding molecule that simultaneously recruited both Dishevelled (Dvl) and protein kinase Cδ (PKCδ) through the membrane-spanning C-terminal region to form a complex that stimulated extracellular signal-regulated kinase (ERK)/activating protein-1 (AP-1) via a PKCδ component but also organised the actin filament via a Dvl component. The KITENIN complex controlled the invasiveness of CRC cells aetiologically harbouring various mutations in APC, β-catenin or K- ras, in which AP-1 activation is redundant but the organisation of the actin filament is indispensable for cell motility. Clinically, KITENIN expression was significantly higher in colon cancer tissues from advanced stage (III, IV) than that of stage I CRC and also in corresponding metastatic tissues. Conclusions: The functional KITENIN complex acts as an executor with regard to cell motility and thereby controls CRC cell invasion, which may contribute to promoting metastasis.